PHOTO-CROSSLINKABLE POLYMER SOLID ELECTROLYTE, CROSSLINKED POLYMER SOLID ELECTROLYTE FILM AND MANUFACTURING METHOD THEREFOR - HAMAMOTO SHIRO; SAKAGUCHI YOSHIMITSU; TAKASE SATOSHI; KITAMURA KOTA; NAKAO JUNKO; NAGAHARA SHIGENORI (2003)
PROBLEM TO BE SOLVED: To provide a polymer solid electrolyte film and a manufacturing method therefor in which not only excellent ion conductivity is exhibited but also durability such as a swelling-resistant property is simultaneously excellent and it can be preferably used for a proton exchange film of a fuel cell or the like. SOLUTION: After a photo-crosslinkable polymer electrolyte having one or more ionic group and photo-crosslinkable group in the molecule respectively is molded into a film, the thermal crosslinkable group is subjected to croslinking reaction by irradiation with light to obtain the polymer solid electrolyte film. The crosslinking reaction can be carried out without accompanying decomposition of the ionic group and the ion conductivity is not reduced by the crosslingking reaction. The polymer solid electrolyte film having excellent ion conductivity and durability can be obtained. COPYRIGHT: (C)2003,JPO